2006
DOI: 10.1111/j.1442-2042.2006.01423.x
|View full text |Cite
|
Sign up to set email alerts
|

Intrascrotal calculi: A very rare stone disease

Abstract: A stone in the hydrocele sac is very rarely encountered, whereas the occurrence of multiple stones in the hydrocele cavity has not been reported before. Numerous intrascrotal stones were encountered in the hydrocele sac of a patient during operation and has prompted us to report this case.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Biochemical analysis of the calculi, on the other hand, showed that they were composed of calcium, oxalate, and phosphorus. 17 In our series, 12 of the 23 patients had no pathologic abnormalities of the scrotal contents except for the scrotal calculi. In 12 patients with no pathologic abnormalities of the scrotum, the other hypothesis based on alterations in the scrotal fluid content may be more appropriate.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Biochemical analysis of the calculi, on the other hand, showed that they were composed of calcium, oxalate, and phosphorus. 17 In our series, 12 of the 23 patients had no pathologic abnormalities of the scrotal contents except for the scrotal calculi. In 12 patients with no pathologic abnormalities of the scrotum, the other hypothesis based on alterations in the scrotal fluid content may be more appropriate.…”
Section: Discussionmentioning
confidence: 56%
“…Parlaktas et al 17 reported multiple calculi in hydrocele along with findings from histopathologic examination of the excised tunica vaginalis testis and biochemical analysis of the calculi. Histologic examination of the tunica vaginalis testis revealed chronic inflammation with fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Histologically, the scrotal calculi consist of fibrinoid deposits around a central nidus of hydroxyapatite (3,8). Biochemical analyses of the calculi have revealed that they are composed of calcium, oxalate and phosphorus (9).…”
Section: Discussionmentioning
confidence: 99%
“…4 But in our case patient presented with the scrotal swelling with no scrotal pain or the hydrocele, ultrasound scrotum also showed hypervascular lesion with no evidence of calculi. Scrotal calculi found in the sac of hydrocele in a case reported by Parlaktas et al and study done by Merino et al 5,6 Due to frerquent use of ultrasound now a days diagnosis of scrotal calculi is more frequently being made. 7 Parlak et al also reported a case of uretheroscrotal fistula that developed after a surgery for uretheral stone removal and cystolithotomy, patient presented with painless scrotal swelling that used to disappear after manual compression, little bit similar as in our case fistula developed after scrotal stone removal but swelling didn't disappear on manual compression but demonstrated clear evidence of scrotourethral fistula as fluid was coming out both from scrotal skin and the urethral meatus (Figure 4), so we made a diagnosis of scrotourethral fisula on clinical basis only, unlike in prior case where they prescribed multidetector CT(MDCT) for the diagnosis.…”
Section: Discussionmentioning
confidence: 95%